ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SELAMA PANDEMI COVID-19 - Hawari, Lilik Ayu; Burhanudin, H. (Universitas Muhammadiyah Mataram, 2024)
This research aims to determine the differences in company financial performance before and during the Covid-19 pandemic in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange as measured by the financial ratios Liquidity (Current Ratio), Leverage (Debt Equity Ratio), Activity (Total Asset Turnover), Profitability (Return On Assets), and Market Ratio (Price Earning Ratio). The period used in this research is four years, starting from 2018-2021.Samples were taken using the purposive sampling method. The population in this research is all food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 period. From a population of 30 manufacturing companies, 24 manufacturing companies were obtained as samples with an observation period of four years (2018-2021). The analytical tools used are descriptive statistical tests, data normality tests and different hypothesis tests, namely the paired sample t test and the Wilcoxon signed ranks test.Based on the results of data analysis, it was concluded that there were no significant differences in the company’s financial performance as measured by CR, DER, TATO, ROA and PER before and during the Covid-19 pandemic.